Engineering an antibacterial nanofibrous membrane containing N-Halamine for recyclable wound dressing application. (June 2020) - Luo, Hao; Yin, Xueqian; Tan, Pengfei; Shi, Yidong; Gu, Yingchun; Zeng, Rui; Tan, Lin
Graphical abstract: Abstract: The exposure of wounds and improper wound care can inevitably increase the occurrence of bacterial infection, thus highlighting the necessity of engineering antibacterial wound dressings due to the increasing demand for accelerating wound healing. In this contribution, we firstly synthesized a novel antibacterial N-halamine incorporated polymer (AP) and followed by the blending of AP and thermoplastic polyurethane (TPU) and the further processing of the blend into nanofibrous membrane (NM) using electrospinning. The synthesized AP and prepared NMs were fully characterized in terms of structure, morphology, mechanical property, surface wettability, UV stability, cytocompatibility and antibacterial performance. Results showed that the prepared NMs show a powerful behavior against Gram positive S. aureus (ATCC6538), Gram negative E. coli (ATCC8739) and fungi involved with Saccharomyces cerevisiae (ATCC9763) and Aspergillus niger (ATCC16404). Furthermore, the rechargeable property of NMs was facilely demonstrated by a chlorination process, during which, the content of active chlorine could regenerate to around 80 % and the reusability of NM was studied in terms of the spinnability and antibacterial performance. Overall, the successful preparation of AP and NMs with desirable antibacterial property, cytocompatibility, processability, and reusability at present holds a great potential for accelerating wound healing in a sustainable and structurally adaptive form.